Exciton‐Exciton Annihilation Dynamics: Excitonic Transport and Intervalley Scattering Dynamics in Large‐Size Exfoliated MoSe2 Monolayer Investigated by Heterodyned Transient Grating Spectroscopy (Laser Photonics Rev. 14(12)/2020). Issue 12 (11th December 2020) - Kuhn, Henning; Wagner, Julian; Han, Shuangping; Bernhardt, Robin; Gao, Yan; Xiao, Liantuan; Zhu, Jingyi; van Loosdrecht, Paul H. M.
Abstract : Exciton intervalley scattering, annihilation, relaxation dynamics, and diffusive transport in monolayer transition metal dichalcogenides (TMDCs) are central to the functionality of devices based on them. In article number 2000029 by Jingyi Zhu, Paul H. M. van Loosdrecht, and co‐workers investigate exciton‐exciton annihilation dynamics and its effect in the distortion of the diffusion grating in an exfoliated monolayer TMDC, MoSe2 .